2019
DOI: 10.1039/c8sm01966e
|View full text |Cite|
|
Sign up to set email alerts
|

Transition rates for slip-avalanches in soft athermal disks under quasi-static simple shear deformations

Abstract: We study slip-avalanches in two-dimensional soft athermal disks by quasi-static simulations of simple shear deformations. Sharp drops in shear stress, or slip-avalanches, are observed intermittently during steady state. Such the stress drop is caused by restructuring of the contact networks, accompanied by drastic changes of the interaction forces, ∆ f . The changes of the forces happen heterogeneously in space, indicating that collective non-affine motions of the disks are most pronounced when slip-avalanches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…In order to describe solid-like granular matter on the macroscopic scale, concepts from elasto-and visco-plastic theories were used [15,16,21,[26][27][28][29][30][31][32][33][34][35] including instabilities, yield and failure [29,[36][37][38][39][40][41][42][43][44][45]. Recently, statistical mechanics/ physics concepts [19,46], helped to better understand the probabilities for plastic deformations [17-21, 34, 47-49], force network change/growth [50,51], stress-based meso ensembles [52], or stress-relaxation [11,[22][23][24]. A traditional subject of research are stress-fluctuations [53][54][55][56], and the quest for the "effective temperature" [47,48,57,58] of thermal or a-thermal granular packings [48,52,59].…”
Section: A Brief History Of Granular Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to describe solid-like granular matter on the macroscopic scale, concepts from elasto-and visco-plastic theories were used [15,16,21,[26][27][28][29][30][31][32][33][34][35] including instabilities, yield and failure [29,[36][37][38][39][40][41][42][43][44][45]. Recently, statistical mechanics/ physics concepts [19,46], helped to better understand the probabilities for plastic deformations [17-21, 34, 47-49], force network change/growth [50,51], stress-based meso ensembles [52], or stress-relaxation [11,[22][23][24]. A traditional subject of research are stress-fluctuations [53][54][55][56], and the quest for the "effective temperature" [47,48,57,58] of thermal or a-thermal granular packings [48,52,59].…”
Section: A Brief History Of Granular Researchmentioning
confidence: 99%
“…There-among other considerations-it is shown that (finite) granular systems can remain elastic for tiny strain, then have localized plastic events at larger strain with probability increasing, before (global) yield takes place with particular probabilities as cast into a meso-scale, stochastic master-equation approach, in Refs. [50,153,154].…”
Section: Granular Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…4. It is plausible that contact changes are a proxy for irreversible rearrangements, but this must be verified-while rearrangements involve contact changes, not all rearrangements are irreversible [22,[30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…To better model the static problem, various static discrete element models have been proposed, in which different formulations are employed to remove inertial effects in DEM . As a consequence, the integration of the equation of motion is avoided, and the system evolves through a series of static equilibrium states under varied loads.…”
Section: Introductionmentioning
confidence: 99%